Running as a form of active leisure - running paths as a substantial element of local society development strategies - Weronika Stodółka; Damian Filipowski; Kamil Michalik; Krzysztof Pałkiewicz; Jacek Stodółka (Kazimierz Wielki University, 2017)
The civilizational progress has brought many conveniences that allowed us to choose leisure and recreation as the preferred way of spending our free time. The interest in the advantages of open-air activities keeps growing, together with the number of needs emerging with the constant improvement of the economic status of our society. Meeting those needs has become the aim of many projects. The more fashionable running becomes, the higher amount of people get interested in it and start running. The dynamic development of tourism related to running is a challenge for the tourism market. The astonishing popularity of this form of sport is especially visible in the number of people taking part in official runs and the growing number of the runs themselves. Promoting the region through active tourism is more than desirable. The goal is to show the right direction in creating the local society development strategies in fields such as health and active leisure for local governments. This direction is the proposition to create more running paths. The way of creating them has been described on the example of Świdnica city in Lower Silesian region ofPoland. The project should perfectly match the development strategy of the city and become helpful for the municipality. Having the area of the city and the number of its inhabitants in mind one could apply the guidelines written above to other cities with similar conditions without hesitation.